(Un)Learning to Be Human? : Collected Essays on Critical Posthumanism, Volume 1 - Herbrechter, Stefan, (Critical Posthumanisms ;, 2025)
Critical posthumanism is a theory paradigm that has become hugely influential across the humanities and social sciences in the last twenty years. This volume collects essays written over the last decade by one of the founders and leading figures of this movement. Originally a reaction to accelerated technological and media change that challenges traditional notions of what it means to be human, posthumanism (as opposed to transhumanism) has developed into a general critique and reappraisal of life after humanism and anthropocentrism. The essays collected here are dealing with aspects of education, technology, politics, media and art, and share a focus on how to critique and unlearn traditional understandings of humanness and (re)learn what it means to be human differently.